y= logex , means log to the base e containing x is equal to y. So when you will inverse this log then the equation will become: e^y =x. That is e to the power y is equal to x. Similarly if log have any

Explanation: Let: logb(x) = y ⇒ switch x and y: logb(y) = x ⇒ solve for y: blogb(y) = bx. y = bx ⇒ hence: logb(x) and bx are the inverse functions. Answer link.

They allow us to solve hairy exponential equations, and they are a good excuse to dive deeper into the relationship between a function and its inverse. Use the logarithm change of base rule

Track Way

This is the perfect place to come for a walk or a run, with a wide track that is well maintained.

You Request? We Answer!

You Ask? We Answer! is a column dedicated to answering all of your burning questions.

Get detailed step-by-step explanations

Looking for detailed, step-by-step answers? Look no further – our experts are here to help.

Replace the function notation fleft ( x right) f (x) by y y. fleft ( x right) to y f (x)

How to find the inverse of a logarithmic function, f (x) = log2 (x) - YouTube. #logarithmicfunctions #brianmclogan.